THE SEMIOTIC ANALYSIS OF PRE-WEDDING RITUALS OF HINDU MARRIAGES PERFORMED IN THE STATE OF BIHAR - Vijay Kumar; Jayal, Jyoti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The paper critically analyses the semiotic dimensions of Hindu pre-wedding rituals performed in the state of Bihar, delving into the meanings and philosophies embedded in these rituals and artifacts associated with them. By interpreting these rituals (symbols), the study seeks to preserve the rich tradition of Indian weddings, with special focus on the traditional and cultural heritage of Bihar. Using Roland Barthes’ theory of semiotics, the study explores how these rituals and artifacts convey layered meaning, reinforce social values, and articulate collective identity within the community. Moreover, the paper also focuses on discussing in brief the impact of modernization, social status and gender in the performance of the hindu pre-wedding rituals. The research employs qualitative methods with an interpretive approach, focussing on the interpretation of the hindu pre-wedding rituals performed in Bihar in relation to its contextual data. The study aims to identify the denotative and connotative meanings of the rituals and artifacts used in these rituals, decoding their relevance within the socio-religious context as cultural myths. The findings suggest that these rituals serve as a cultural text, embodying historical continuity, spiritual significance, and social stratification. By applying semiotic analysis, the study provides a nuanced understanding of how these rituals contribute to the construction of collective identities, familial bonds, and cultural heritage in a rapidly modernizing society.